2005
DOI: 10.1177/0885328205047397
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Endothelial Cells in vitro on Paclitaxel-loaded Coronary Stents

Abstract: Coronary stents that are developed for use with balloon angioplasty are known to cause acute occlusion and long-term stenosis. It is likely that a controlled release of drugs at the site of stent implantation might inhibit the proliferation of vascular smooth muscle cells (VSMC) and reduce restenosis. However, if the drug is necrotic and affects cell survival near the implant, it may interrupt the local tissue regeneration. Different methods have been used for the immobilization of drugs with stents to get an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This study confirms earlier results from Prasad et al [44,45] advocating the need of multiple layers of coatings to optimize the in vitro and in vivo results obtained with paclitaxel. Basically, the stents were sandwiched in 3 layers of coating, with only the two layers closest to the metallic frame containing elutable drugs.…”
Section: Discussionsupporting
confidence: 91%
“…This study confirms earlier results from Prasad et al [44,45] advocating the need of multiple layers of coatings to optimize the in vitro and in vivo results obtained with paclitaxel. Basically, the stents were sandwiched in 3 layers of coating, with only the two layers closest to the metallic frame containing elutable drugs.…”
Section: Discussionsupporting
confidence: 91%
“…They also confirmed that in an appropriate concentration range, paclitaxel did not cause necrosis of the surrounding tissue and did not affect the healing and epithelialization of the tracheal mucosa. [2526]…”
Section: Discussionmentioning
confidence: 99%
“…21 Others have shown that apoptosis is induced in human umbilical vein endothelial cells grown for 72 hours on paclitaxel eluting stents. 36 However, minimal induction of apoptosis was observed by paclitaxel. TNF-a did not enhance apoptosis nor did it interact with paclitaxel.…”
Section: Discussionmentioning
confidence: 99%